2016
DOI: 10.1242/jcs.178236
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic distributions of long double-stranded RNA in Tetrahymena during nuclear development and genome rearrangements

Abstract: Bi-directional non-coding transcripts and their ∼29-nt small RNA products are known to guide DNA deletion in Tetrahymena, leading to the removal of one-third of the genome from developing somatic nuclei. Using an antibody specific for long double-stranded RNAs (dsRNAs), we determined the dynamic subcellular distributions of these RNAs. Conjugation-specific dsRNAs were found and show sequential appearances in parental germline, parental somatic nuclei and finally in new somatic nuclei of progeny. The dsRNAs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…A more direct evidence was provided by fCLIP‐seq analysis using J2 antibody to directly capture and sequence dsRNAs in HeLa cells. J2 antibody specifically recognizes dsRNAs longer than ≈40 bp and has been widely used to visualize viral dsRNAs and to study endogenous dsRNAs in animal models such as worm and mouse . Using J2 fCLIP‐seq, the authors found that most of the sequencing reads were mapped to SINE elements (≈80%) that were all heavily edited .…”
Section: What Are the Endogenous Dsrnas And How Are They Recognized?mentioning
confidence: 99%
“…A more direct evidence was provided by fCLIP‐seq analysis using J2 antibody to directly capture and sequence dsRNAs in HeLa cells. J2 antibody specifically recognizes dsRNAs longer than ≈40 bp and has been widely used to visualize viral dsRNAs and to study endogenous dsRNAs in animal models such as worm and mouse . Using J2 fCLIP‐seq, the authors found that most of the sequencing reads were mapped to SINE elements (≈80%) that were all heavily edited .…”
Section: What Are the Endogenous Dsrnas And How Are They Recognized?mentioning
confidence: 99%
“…Furthermore, studies in Tetrahymena and Paramecium revealed that IES excision occurs through RNA-induced heterochromatin formation rather than via a transposition-like process (Madireddi et al 1996;Mochizuki et al 2002;Yao et al 2003;Betermier and Duharcourt 2014). In Tetrahymena, dsRNA is transcribed from IESs during conjugation and processed into ∼27-nucleotide (nt) small RNAs called scnRNAs (scan RNAs) (Chalker and Yao 2001;Malone et al 2005;Mochizuki and Gorovsky 2005;Woo et al 2016). scnRNAs then interact with an Argonaute protein (Mochizuki et al 2002) and target homologous IESs, leading to histone modifications, including H3K9me3 and H3K27me3 (Taverna et al 2002;Liu et al 2007), and recruitment of chromodomain proteins Pdd1p and Pdd3p (Madireddi et al 1996;Coyne et al 1999;Nikiforov et al 2000) to form heterochromatin structures that are then deleted.…”
mentioning
confidence: 99%
“…The clustered arrangement of these IESs and the use of the resultant small ncRNAs in targeting TEs resemble the properties of piRNA clusters found in animals [15,19]. Transcription of both DNA strands by Pol II produces complementary transcripts, which form double-stranded RNA (dsRNA) molecules [20][21][22][23]. The dsRNAs are cleaved into 28-30 nt scan RNAs (scnRNAs) by a dicer-like protein, Dcl1 [24][25][26].…”
Section: Introductionmentioning
confidence: 82%
“…Unlike dsRNAs are processed to scnRNAs by Dcl1 [23]. The comparable steady-state levels of ncRNAs in WT and rib1D cells (Figure 2F) suggest that ncRNA transcription is reduced in rib1D and/or ncRNA is destabilized by some degradation pathways in the absence of RIB1.…”
Section: Rib1 Directs the Ncrna Transcription Machinery To The Pericementioning
confidence: 95%
See 1 more Smart Citation